Coherence, efficiency, and independence of the EU environmental policy system: results of complementary statistical and econometric analyses - Fabio Zagonari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
This paper presents the first empirical test of coherence (i.e., consistency of policies within a framework), efficiency (i.e., ability of policies to meet their objectives), and independence (i.e., logical priority of objectives over policies) of the overall EU environmental policy system. To do so, I applied statistical (cross-sectional and time series) and econometric (dynamic tri-probit) analyses to an original panel dataset, based on addressed issues rather than on implemented policies. In contrast with previous studies of single EU environmental policies, characteristics of the EU environmental policy, or EU environmental objectives, I found that the overall EU environmental policy system is coherent, efficient, and independent. Moreover, the evidence suggests that many issues are correlated: trans-boundary issues became more relevant in 2012, pollution production was more significant than resource use, and flow issues were more important than stock issues from 1995 to 2010. Finally, I show that few objectives overlapped: a "safe environment" objective (1987 to 1997) was preferred to a "greenhouse gas (GHG) reduction" objective (2003 to 2012, but pursued with a 2-year lag), although the latter has recently become preferred to the former. In addition, a "GHG reduction" objective was preferred to "a sustainable development" objective (1998 to 2002).
Keywords: Q28; Q38; Q48; Q58; 330